2014
DOI: 10.1097/bcr.0b013e31829b330a
|View full text |Cite
|
Sign up to set email alerts
|

Challenging the Dogma

Abstract: Hypertrophic scarring (HTS) is defined as a scar, which is raised above the skin level and remains within the confines of the original lesion. The authors hypothesize that small surface area burns can be left to heal beyond 21 days without an increase in the incidence of HTS formation, within the confines of a carefully selected patient population. The authors have documented the number of days to healing in all patients conservatively managed in their outpatient burns clinic. All patients who took longer than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Several published studies consist of retrospective case note reviews where any documentation of a scar which is red or raised constitutes a diagnosis of HTS [5, 9]. Other studies use the height of the scar alone [10, 11] or VSS [12] to diagnose HTS. In addition, some papers consider hypertrophic scars alone whereas others combine HTS with contracted or keloid scars to give an overview of pathological scarring [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several published studies consist of retrospective case note reviews where any documentation of a scar which is red or raised constitutes a diagnosis of HTS [5, 9]. Other studies use the height of the scar alone [10, 11] or VSS [12] to diagnose HTS. In addition, some papers consider hypertrophic scars alone whereas others combine HTS with contracted or keloid scars to give an overview of pathological scarring [13].…”
Section: Discussionmentioning
confidence: 99%
“…Thompson et al showed that HTS was more common in American Indian/Alaskan Native race (and also in TBSA >20% and facial burns) but were unable to identify the genetic variant responsible for this finding [12]. A recent study from the UK has failed to show a clear link between skin type and incidence of HTS, but this study included small numbers of non-white patients; just 18 of 181 patients had a Fitzpatrick skin type of 4 or above [11]. …”
Section: Discussionmentioning
confidence: 99%
“…The dysbiotic skin microbiota heighten skin inflammatory responses. When a wound becomes infected, and not properly treated, it takes significantly longer time to heal [132,133].…”
Section: Multiple Nano-drug Delivery Systems For Simultaneous Leishma...mentioning
confidence: 99%
“…Burns that fully re-epithelialise before this point have a low risk of developing hypertrophic scars (and an especially low risk if healed within 2 weeks), whilst those requiring greater than 3 weeks are highly likely to scar. Although more recent research has somewhat challenged this doctrine by finding lower rates of scarring amongst the latter group than previously reported [32]—a change some authors attribute anecdotally to the increasing use of silver-impregnated dressings [31]—burns clinicians still overwhelmingly agree that prolonged healing is a major predictor for scar formation and regard any methods aimed at accelerating re-epithelisation as worthy of consideration.…”
Section: Introductionmentioning
confidence: 99%